Natural Gas and Renewable Methane for Powertrains Future Strategies for a Climate-Neutral Mobility - van Basshuysen, Richard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on natural gas and synthetic methane as contemporary and future energy sources. Following a historical overview, physical and chemical properties, occurrence, extraction, transportation and storage of natural gas are discussed. Sustainable production of natural gas and methane as well as production and storage of synthetic methane are scrutinized next. A substantial part of the book addresses construction of vehicles for natural and synthetic methane as well as large engines for industrial and maritime use. The last chapters present some perspectives on further uses of renewable liquid fuels as well as natural gas for industrial engines and gas power plants.
Forewords.-Climate Neutral Mobility - Natural Gas and Methane as Part of the Solution ,- Historical Overview -- Natural Gas and Renewable Methane -- Vehicle Development for Natural Gas and Renewable Methane -- Off-Highway Gas Engines -- Natural Gas is Caviar for the Engine.
Keywords: Automotive engineering; Transportation engineering; Traffic engineering; Engines; Automotive Engineering; Transportation Technology and Traffic Engineering; Engine Technology